Fuzzy PID Control of Brushless Motors in Positive Pressure Respiratory Protective Masks - ZHAO Xintong; GUAN Jianhui; HU Yongxin; WANG Tianyu (Journal of Harbin University of Science and Technology)
Positive pressure respiratory protection mask is used as individual protective equipment for health care workers to protect against the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). In this paper, the interference of respiratory disturbance and other factors on the air delivery subsystem is ignored, and the mathematical model of Brushless DC motor in the air delivery subsystem is established as the research object. The Brushless DC motor speed PID control model is established in MATLAB/Simulink environment. However, due to the nonlinear and time-varying characteristics of Brushless DC motor, the control effect of PID control on Brushless DC motor in the air supply subsystem is not ideal. The simulation experiment results show that the stability of using fuzzy PID control system is better than that of PID control system, and the control performance of Brushless DC motor is improved.